A population-based study on prevalence and predisposing risk factors of infant functional gastrointestinal disorders in a single center in Southern Fujian - Huang, Huanhuan; Wang, Caiyun; Lin, Wei; Zeng, Yongbin; Wu, Bin (Frontiers in Pediatrics, 2022)
Background and aim The prevalence of infant functional gastrointestinal disorders (FGIDs) varies across different areas but is largely unknown in southern Fujian. The aim of this study is to evaluate the prevalence of infant FGIDs in southern Fujian according to Rome IV diagnostic criteria. Methods A cross-sectional prospective questionnaire-based survey was conducted among healthy infants between 0 and 3 months of age in southern Fujian. A total of 1,006 infants who received a physical examination from October 2017 to October 2018 were recruited in this study. Parents or caregivers provided demographic information and completed the questionnaire on gastrointestinal symptoms for infants. Infants with FGIDs were diagnosed using the Rome IV criteria. Results Based on the Rome IV criteria, the prevalence of having a FGID in infants is 58.3% (586/1,006). The most common FGIDs in infants were regurgitation (45.7%, 460/1,006), followed by difficult defecation (3.6%, 36/1,006), functional constipation (3.2%, 32/1,006), and colic (2.4%, 24/1,006). No infants fulfilled diagnostic criteria for rumination syndrome and cyclic vomiting syndrome. Among the infants with FGIDs, 457 cases (78.0%, 457/586) were found with single FGID. Combined FGIDs were diagnosed in 129 (22.0%, 129/586) infants; of whom, 21.2% (124/586) had double disorders and 0.9% (5/586) had triple disorders. The most common combined FGIDs were regurgitation and difficult defecation (12.8%), followed by regurgitation and colic (2.4%). Risk factor analysis revealed that younger paternal age (B = 0.424, P = 0.004), paternal history of FGIDs (B = 0.821, P = 0.000), maternal history of FGIDs (B = 0.427, P = 0.012), and probiotics received in infant (B = 0.324, P = 0.032) were associated with an increased risk of infant FGIDs, whereas vitamin D supplementation after birth (B = −0.690, P = 0.000) can reduce the risk of developing FGIDs. Conclusion FGIDs are common in infants living in southern Fujian according to Rome IV diagnostic criteria. The most common FGIDs in infants were regurgitation, difficult defecation, and functional constipation. Factors including younger paternal age, parental history of FGIDs, and the probiotic supplementation in infant showed a significant association with infant FGIDs. Whereas, vitamin D supplementation in infant was found to be a protective factor against FGIDs.